Decentralized control for l2 weak string stability of vehicle platoon. Issue 1 (July 2017) - Ferguson, Joel; Donaire, Alejandro; Knorn, Steffi; Middleton, Richard H.
Abstract: In this paper we present a method of bidirectional control of a vehicle string that achieves l 2 weak string stability. Previous work required short-range communications between vehicles within the string. Here, we utilise some recent results on integral action to remove the requirement of communications altogether.